Stem Cell Factor in Combination with Granulocyte Colony-Stimulating Factor reduces Cerebral Capillary Thrombosis in a Mouse Model of CADASIL. Issue 4 (April 2018) - Ping, Suning; Qiu, Xuecheng; Gonzalez-Toledo, Maria E; Liu, Xiaoyun; Zhao, Li-Ru
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy (CADASIL) is a cerebral small vascular disease caused by NOTCH3 mutation-induced vascular smooth muscle cell (VSMC) degeneration, leading to ischemic stroke and vascular dementia. Our previous study has demonstrated that repeated treatment with a combination of stem cell factor (SCF) and granulocyte colony-stimulating factor (G-CSF) reduces VSMC degeneration and cerebral endothelial cell (EC) damage and improves cognitive function in a mouse model of CADASIL (TgNotch3R90C). This study aimed to determine whether cerebral thrombosis occurs in TgNotch3R90C mice and whether repeated SCF+G-CSF treatment reduces cerebral thrombosis in TgNotch3R90C mice. Using the approaches of bone marrow transplantation to track bone marrow-derived cells and confocal imaging, we observed bone marrow-derived blood cell occlusion in cerebral small vessels and capillaries (thrombosis). Most thrombosis occurred in the cerebral capillaries (93% of total occluded vessels), and the thrombosis showed an increased frequency in the regions of capillary bifurcation. Degenerated capillary ECs were seen inside and surrounding the thrombosis, and the bone marrow-derived ECs were also found next to the thrombosis. IgG extravasation was seen in and next to the areas of thrombosis. SCF+G-CSF treatment significantly reduced cerebral capillary thrombosis and IgG extravasation. These data suggest that the EC damage is associated with thrombosis and blood–brain barrier leakage in the cerebral capillaries under the CADASIL-like condition, whereas SCF+G-CSF treatment diminishes these pathological alterations. This study provides new insight into the involvement of cerebral capillary thrombosis in the development of CADASIL and potential approaches to reduce the thrombosis, which may restrict the pathological progression of CADASIL.